THE EFFECTIVENESS OF THE PRINCIPLE OF AMPLE DEFENSE IN BRAZILIAN PROCEDURAL LAW (CIPEEX, 2025)
The guarantee of ample defense is a principle enshrined in the Brazilian legal system, fundamental to ensuring a fair and equitable trial. In this context, there is a need to investigate whether this principle has been effectively observed in the practice of Brazilian procedural law. Has the principle of ample defense been fully implemented in Brazilian procedural law? This is the central question that guides this study, motivating a detailed analysis of the application and observance of this principle in the different spheres of the Brazilian legal system. The general objective of this study is to analyze whether the principle of ample defense has been effectively observed and applied in Brazilian procedural law, identifying challenges and prospects for its full implementation. The following specific objectives were formulated: i) to discuss the doctrinal concept of the principle of ample defense, elucidating its importance and scope in the Brazilian legal context; ii) to investigate the legal provision of the principle of ample defense, both in national legislation and in international treaties ratified by Brazil; iii) to analyze practical and jurisprudential cases to verify the application of the principle of ample defense in different instances of the Brazilian legal system. The research is based on a qualitative analysis of normative, doctrinal and jurisprudential sources related to the principle of ample defense in Brazilian procedural law. Legislation, international treaties, legal works and relevant court decisions will be consulted to support the analysis and conclusions of this study. The importance of the principle of ample defense in the Brazilian legal context cannot be underestimated. Ensuring that all parties involved in a case have the opportunity to defend themselves is essential to promoting justice and fairness in legal relations. In addition, compliance with this principle strengthens the democratic foundations of the Brazilian legal system, contributing to the consolidation of the rule of law. The analysis of the results reveals that, although the principle of ample defense is enshrined in law and doctrine, its implementation in practice is not always guaranteed. Individuals often have to resort to the courts to guarantee the full exercise of this fundamental right. Cases of violation of the principle of ample defense, such as the annulment of administrative acts due to non-compliance, highlight the need for greater attention and vigilance in relation to this issue.
Keywords: principle of ample defense; brazilian procedural law; due process of law; violation of rights